2020
DOI: 10.1073/pnas.2001665117
|View full text |Cite
|
Sign up to set email alerts
|

Nur77 controls tolerance induction, terminal differentiation, and effector functions in semi-invariant natural killer T cells

Abstract: Semi-invariant natural killer T (iNKT) cells are self-reactive lymphocytes, yet how this lineage attains self-tolerance remains unknown. iNKT cells constitutively express high levels of Nr4a1-encoded Nur77, a transcription factor that integrates signal strength downstream of the T cell receptor (TCR) within activated thymocytes and peripheral T cells. The function of Nur77 in iNKT cells is unknown. Here we report that sustained Nur77 overexpression (Nur77tg Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

0
17
0

Year Published

2020
2020
2024
2024

Publication Types

Select...
5

Relationship

0
5

Authors

Journals

citations
Cited by 18 publications
(17 citation statements)
references
References 76 publications
(161 reference statements)
0
17
0
Order By: Relevance
“…In these mice, the transcriptional activity of all three NR4As is inhibited in thymocytes, resulting in reduction of apoptosis after TCR stimulation and increasing numbers of CD4 + CD8 − thymocytes [32,62]. Next, mice were generated with constitutively overexpressed Nur77 in thymocytes showing a large decrease in thymocytes, specifically immature CD4 + CD8 + , but also CD4 + CD8 − and CD4 − CD8 + thymocyte numbers were lower [63,64]. The number of CD4 − CD8 − thymocytes showed no difference when using mice with Nur77 overexpression in multiple studies [61,63,65], whereas one study observed an increase [66] and another lower numbers [64].…”
Section: In Vivo Studies Showing a Role For Nur77 In Thymocyte Selectmentioning
confidence: 99%
See 4 more Smart Citations
“…In these mice, the transcriptional activity of all three NR4As is inhibited in thymocytes, resulting in reduction of apoptosis after TCR stimulation and increasing numbers of CD4 + CD8 − thymocytes [32,62]. Next, mice were generated with constitutively overexpressed Nur77 in thymocytes showing a large decrease in thymocytes, specifically immature CD4 + CD8 + , but also CD4 + CD8 − and CD4 − CD8 + thymocyte numbers were lower [63,64]. The number of CD4 − CD8 − thymocytes showed no difference when using mice with Nur77 overexpression in multiple studies [61,63,65], whereas one study observed an increase [66] and another lower numbers [64].…”
Section: In Vivo Studies Showing a Role For Nur77 In Thymocyte Selectmentioning
confidence: 99%
“…Next, mice were generated with constitutively overexpressed Nur77 in thymocytes showing a large decrease in thymocytes, specifically immature CD4 + CD8 + , but also CD4 + CD8 − and CD4 − CD8 + thymocyte numbers were lower [63,64]. The number of CD4 − CD8 − thymocytes showed no difference when using mice with Nur77 overexpression in multiple studies [61,63,65], whereas one study observed an increase [66] and another lower numbers [64]. The inconsistent results obtained from these studies are most likely due to the use of different TCR transgenic backgrounds, type of T cells studied, and the stimulations applied in the accompanying in vitro experiments.…”
Section: In Vivo Studies Showing a Role For Nur77 In Thymocyte Selectmentioning
confidence: 99%
See 3 more Smart Citations